Effect of Sodium Dodecyl Sulfate on the Continuous Crystallization in Microfluidic Devices Using Microbubbles. Issue 10 (1st July 2019) - Fatemi, Naghmeh; Devos, Cedric; De Cordt, Glenn; Van Gerven, Tom; Kuhn, Simon
Abstract: Introducing microbubbles in a microreactor for continuous crystallization increases the nucleation rate and also prevents clogging. Adding surfactants affects the microbubble generation as it reduces their size, increases their frequency of formation and consequently also the interfacial area per unit volume of reactor acting as heterogeneous surface for nucleation. Here, the effect of sodium dodecyl sulfate (SDS) on both the microbubble generation and the continuous crystallization of paracetamol is investigated. It is observed that while SDS significantly enlarges the heterogeneous surface available for nucleation, the crystallization itself is inhibited by its presence. Abstract : Microbubbles enhance nucleation in continuous crystallization in microfluidic devices by introducing a heterogeneous nucleation site. Adding sodium dodecyl sulfate as a surfactant introduces smaller microbubbles which results in higher microbubble surface area per unit volume of the reactor. However, despite this increase, the addition of this surfactant showed hindering effects for nucleation.